A rendőrség társadalmi szerepe szociológiai szempontból - Krémer, Ferenc (Szociológiai Szemle, 2024)
Of the factors determining the organisation and operation of the police one of the most important is the dominant concept of the social role of the police. The paper attempts to describe the three existing types and a hypothetical one of the role models.War on crime commissions the police to retain social borders, as a result the police are organised as an army and their most important role is control over the society. This model only expects the policeman to be able to apply coercion.Whereas order maintenance focuses on conflict treatment. It interprets social problems from the angle of order valid for all. It is for the first time in this model that the qualifications of policemen and of social science become important to the proper functioning of the police, in keeping with their social role.Relationship to the community is in the centre of the third model. Social service to the public means that the police accept it and consider it the measure of their activities that they are unable to maintain order without the co-operation of the citizens. The police become part of the community of citizens and produce security of the community.As part of the mechanism of integration the police strive not to let confrontation replace consensus. In the emerging multicultural society it is their social role to control the co-operation of different values and ways of life based on pluralism and tolerance.